A Local Wisdom-Based E-Module to Enhance Students’ Learning Interest and Achievement - Septiani, Rahma Dwi; Rahmawati, Nafissa Citra; Nooralicia, Dinda Febrianissa; Rizqi, Arfa’a; Setiawaty, Rani (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objective: This study investigates the role of local wisdom-based e-modules in improving students’ learning interest and academic achievement within contextual learning environments. Local culture is embedded in e-learning modules to make learning materials more relevant and meaningful to students’ daily lives. Research Methodology: A Systematic Literature Review (SLR) method was employed, consisting of five stages: analysis, design, development, implementation, and evaluation. Using the Publish or Perish (PoP) tool, the researchers collected secondary data from Google Scholar between 2015 and 2025. From an initial pool of 200 articles, 20 relevant studies were selected for in-depth analysis. Findings/Results: The findings demonstrate that integrating local cultural elements such as folklore, local flora and fauna, traditional values, and regional wisdom into e-modules significantly enhances students’ learning motivation and outcomes across different educational levels. These modules also encourage independent learning and support character development. Conclusion/Recommendations: Local wisdom-based e-modules offer an effective and sustainable solution for promoting meaningful and culturally responsive education. They enhance the relevance of learning materials while also contributing to the preservation of local culture. It is recommended that educational institutions adopt these modules more widely to improve educational quality and cultural awareness.